2007
DOI: 10.2224/sbp.2007.35.8.1121
|View full text |Cite
|
Sign up to set email alerts
|

The Moderation Effect of Hr Strength on the Relationship Between Employee Commitment and Job Performance

Abstract: In this study a hierarchical linear model was employed to identify the specific relationships between employee affective commitment, employee perceptions of HR practices and job performance, and the moderating effect of HR strength was examined, using the extent to which employers and employees share the same perceptions of HR practices as a proxy for consistency. The data were collected via structured questionnaire from hairdressing salons throughout Taiwan. Usable questionnaires from 307 hairdressers and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…This study found that positive organizational support had a strong positive relationship towards affective commitment and continuance commitment, whilst a small negative relationship to normative commitment. Researchers argued that the level of employee commitment is also affected by employees' perception of organizational support and security of employment with an organization (Kacmar et al, 2003;Chen et al, 2007).…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that positive organizational support had a strong positive relationship towards affective commitment and continuance commitment, whilst a small negative relationship to normative commitment. Researchers argued that the level of employee commitment is also affected by employees' perception of organizational support and security of employment with an organization (Kacmar et al, 2003;Chen et al, 2007).…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Several studies found that organizational support and the relationship between employer and employee affect employees' satisfaction (Karrasch, 2003;Karsh, Booske, & Sainfort, 2005) and organizational commitment (Karrarsch, 2003). The level of the organizational commitment is affected by employees' perception of organizational support and security of employment with an organization (Chen, Lin, Lu, & Taso, 2007;Kacmar, Witt, Zivnuska, & Gully, 2003); the more satisfaction and commitment the employees have, the more successful the organization will be in reaching their goals and gaining a competitive advantage. Mowday, Porter, and Steers (1982) argued that without a significant level of employee commitment, an organization will not survive.…”
Section: Introducationmentioning
confidence: 99%
“…Prior studies that follow this conceptual model have often focused on development of HRM strength measures (Coelho, Cunha, Gomes, & Correia, ; Delmotte, De Winne, & Sels, ; Gomes, Jorge, Coelho, Correia, & Cunha, ), or conducting partial tests of the theory by examining the relationships between some of the metafeatures and employees’ intentions and attitudes (S. J. Chen, Lin, Lu, & Tsao, ; Li et al, ; Sanders et al, ) and organizational performance (Cunha & Cunha, ; Cunha, Cunha‐Kintana, Morgado, & Brewster, ). However, these efforts have as yet been preliminary and limited in their scope.…”
Section: Examining the Relationships Between Mbo System Strength And mentioning
confidence: 99%
“…According to Wasti (2003:304), affective commitment has the strongest and most consistent difference with advantageous outcomes for the organisation, and this has been very well researched. This is confirmed by the meta-analyses conducted by Mathieu and Zajac (1990), who suggest that the majority of research indicates that affective commitment can be expected to have the strongest positive impact upon desirable employee behaviours and, according to Chen et al (2007Chen et al ( :1130, on job performance. OC at the same time provides employees with stability and feelings of belonging and thereby contributes to reduced stress and increased health and well-being in organisations (Mathieu & Zajac 1990;Siu 2002).…”
Section: Discussionmentioning
confidence: 75%